The scientific production of Kombucha: a global bibliometric review - Almeida , Katcilanya Menezes de; Paixão, Gean Carlos Targino; Ribeiro , Radmila Raianni Alves; Espírito Santo , Maria Luciete Barbosa do; Costa , Rikaelly Vital; Silva , Júlio César Bezerra Vilar da; Neves , Bárbara Araújo; Cruz , Ana Clara Silva da; Lira , Myrella Cariry; Santos , Edilayane da Nóbrega; Andrade , Gabriela Paes Barreto de; Ribeiro , Neila Lidiany (Food Science and Technology, 2025)
Kombucha, a fermented beverage obtained from the fermentation of green tea sweetened by a symbiotic culture of bacteria and yeasts, has aroused growing interest due to its antioxidant, antimicrobial, and probiotic properties and diversity of applications. In this context, this study carries out a bibliometric analysis of scientific production on Kombucha between 2000 and 2025, using indexed databases to map research trends, the most influential authors, collaboration networks, and predominant themes. The results show a significant increase in the number of publications in recent years, with a greater concentration of studies from 2016 onward. The main countries producing knowledge on Kombucha include the United States, China, and Brazil, with relevant international collaborations. The most frequently addressed topics involve the chemical and microbiological characterization and bioactive compounds of the beverage, as well as investigations into food safety and the development of new derivative products. The analysis of co-authorship networks revealed the existence of consolidated research groups, especially renowned institutions in the field of food science and technology. The findings of this study reinforce Kombucha as an emerging and interdisciplinary topic, pointing to opportunities for future research aimed at innovation, optimization of fermentation processes, and evaluation of benefits to human health.